Price transmission in vertically-related markets - Weldegebriel, Habtu Tadesse (2004)
The thesis aims to contribute to the literature on two fronts. Firstly, it aims to contribute to the literature by developing a conjectural variations model of price transmission in vertically related markets where the final product sector exercises both oligopoly power and oligopsony power. It finds that oligopoly and oligopsony power do not necessarily weaken the degree of price transmission relative to that under perfectly competitive markets although they can. The key to these outcomes is to be found in the functional forms for retail demand and farm supply.